IDEOLOGI MASYARAKAT MADURA DALAM UNGKAPAN-UNGKAPAN IDIOMATIS - - Hani'ah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2010)
Critical linguists, like Volosinov, Bakhtin, Foucault, Fairclough, Wodak, Kress, Hodge, dan Van Dijk believe that language is an ideology and ideoligic. Language ideology used in societies is considered a commonsensicalthought. It is often used as the guidance to perform certain acts, by the members of societies to obtain harmony. The idiomatic expressiant social life is the Madurese, is one of the society which is still used idiomatic expressions in their social life. And the writer interested to take an idiomatic expressions at the object of her study. This study applies the saussure’s semiotic approach. Saussure claims that language is a system of signs reflecting social life. Hence, signs contain social aspecs applied in societies, known as ideology. By applying the Saussure’s approach, the writer found out that the Madurese idiomtic expression contain the ideology of Madurese.